Efficacy and Safety of Endovascular Treatment in Acute Tandem Carotid Occlusions: Analysis of a Single-Center Cohort - Santiago Fernández Menéndez; Eduardo Murias Quintana; Pedro Vega Valdés; Edison Morales Deza; Elena López-Cancio; Lorena Benavente Fernández; Montserrat González Delgado; Maria Rico-Santos; Sergio Calleja Puerta; Davinia Larrosa Campo (Cerebrovascular Diseases Extra, 2020)
Introduction: Acute ischemic strokes with tandem occlusions, which represent 10–20% of all ischemic strokes, have a particularly poor prognosis. Since emergent treatment of tandem lesions has not been specifically addressed in randomized trials, there is an absence of standardized management. Objective: We sought to assess the efficacy and safety of acute endovascular treatment in stroke due to tandem occlusions in our center and compare the results with previous reports. Methods: From a prospective registry we analyzed data of 99 consecutive patients (males: 77.7%, mean age ± SD: 67.5 ± 9.5 years) with stroke due to tandem occlusions who underwent treatment with emergent carotid stenting and intracranial mechanical thrombectomy. Successful recanalization was defined as a TICI score of 2b-3 and a good functional outcome was defined as a modified Rankin scale score ≤2 at 90 days. Symptomatic intracranial hemorrhage (sICH) was considered when associated with worsening on the National Institutes of Health Stroke Scale (≥4 points). Results: A successful recanalization rate was achieved in 87.8 and 48.5% of the patients had a good functional outcome. sICH and mortality rates were 12.1 and 20.2%, respectively, and 21.2% of the patients received combined treatment with intravenous thrombolysis, which did not affect neither the prognosis nor the recanalization or sICH rates. The time from symptom onset to recanalization and the degree of recanalization were the main factors associated with prognosis and the occurrence of sICH. Conclusions: Our results suggest that endovascular treatment with emergent carotid stenting and intracranial thrombectomy in patients with acute stroke due to tandem occlusions is an effective and safe procedure.